Rural and socioeconomic differences in the effectiveness of the HEART Pathway accelerated diagnostic protocol. (3rd January 2023) - O'Neill, James C.; Ashburn, Nicklaus P.; Paradee, Brennan E.; Snavely, Anna C.; Stopyra, Jason P.; Noe, Greg; Mahler, Simon A.
Abstract: Background: The HEART Pathway is a validated accelerated diagnostic protocol (ADP) for patients with possible acute coronary syndrome (ACS). This study aimed to compare the safety and effectiveness of the HEART Pathway based on patient rurality (rural vs. urban) or socioeconomic status (SES). Methods: We performed a preplanned subgroup analysis of the HEART Pathway Implementation Study. The primary outcomes were death or myocardial infarction (MI) and hospitalization at 30 days. Proportions were compared by SES and rurality with Fisher's exact tests. Logistic regression evaluated for interactions of ADP implementation with SES or rurality and changes in outcomes within subgroups. Results: Among 7245 patients with rurality and SES data, 39.9% (2887/7245) were rural and 22.2% were low SES (1607/7245). The HEART Pathway identified patients as low risk in 32.2% (818/2540) of urban versus 28.1% (425/1512) of rural patients ( p  = 0.007) and 34.0% (311/915) of low SES versus 29.7% (932/3137) high SES patients ( p  = 0.02). Among low‐risk patients, 30‐day death or MI occurred in 0.6% (5/818) of urban versus 0.2% (1/425) rural ( p  = 0.67) and 0.6% (2/311) with low SES versus 0.4% (4/932) high SES ( p  = 0.64). Following implementation, 30‐day hospitalization was reduced by 7.7% in urban patients (adjusted odds ratio [aOR] 0.76, 95% confidence interval [CI] 0.66–0.87), 10.6% in low SES patients (aOR 0.68, 95% CI 0.54–0.86), and 4.5% in high SES patients (aOR 0.83, 95% CI 0.73–0.94). However, rural patients had a nonsignificant 3.3% reduction in hospitalizations. Conclusions: HEART Pathway implementation decreased 30‐day hospitalizations regardless of SES and for urban patients but not rural patients. The 30‐day death or MI rate was similar among low‐risk patients.